O trabalho educativo de est??mulo ?? leitura do grupo ria: literatura e teatro no ensino m??dio. - Kassab, Patr??cia Montanholi (2012)
This study looks at performances of literary works by the Ria Theater Group (Grupo de Teatro Ria) to encourage high school students to read. The motivation behind this study come not only from the restlessness coming from literature classes in schools, whose methodology consolidates a stagnant model of memorizing information that is fragmented from the content of subjects, it also comes from reports about the aforementioned group, which aims to encourage students to read, to understand literary works, and to reflect on the human condition. Using data collected by studies on reading and access to cultural assets, reading and theater practices are known to have proven themselves as weak and unsatisfactory. This occurs either because having in interest in these practices has not been learned or because students do not understand the language of these texts. Therefore, using a survey of the field, of documents and of bibliography, the goal was to study and understand this group's working process and the manner in which it contributes to schools regarding reading of more sophisticated texts. The research considered Edgar Morin's studies on complexity as a theoretical support, using the following as a basis: aesthetic, prosaic and poetic states, as well as operators of complexity; because this approach was understood as recognizing the single and multiple being, the multidimensional universe, the need to reconnect findings and a teaching-learning experience that provides an investigative activity geared towards unveiling the complexity of phenomena. This reached some findings: The Ria Theater Group collaborated with the work of schools to encourage student readers; this encouragement was basically given through the language used to adapt these works of literature to the theater, creating interaction between the play and the students; the language of the theater helped in understanding classical texts, since it related themes to life; this relationship heightened critical sense and made it possible to reflect on the human condition, awakening an interest in reading, and this created guidance rather than an obligation; the Ria Theater Group develops "educational teaching" work, which informs while at the same time allowing us to understand our condition, helping us to live.